Investigating the structural, electronic, and optical properties of the novel double perovskite K2AgBiI6 using DFT - Karouchi, Mohamed; Ejjabli, Abdelkebir; Bajjou, Omar; Guerroum, Jamal; Al-Hattab, Mohamed; Basyooni-M. Kabatas, Mohamed A.; Rahmani, Khalid; Lachtioui, Youssef (Frontiers in Materials, 2024)
In this groundbreaking study, we unveil the remarkable structural, electronic, and optical Properties of the newly discovered double perovskite material, K2AgBiI6, presenting a paradigm shift in materials science. The unique crystal structure and diverse atomic interactions inherent in this double perovskite make it an up-and-coming candidate for various technological applications, particularly in photovoltaics; owing to its stability and resistance to heat and humidity, we aim to shed light on the extraordinary potential of K2AgBiI6. Our study provides valuable insights for researchers engaged in tailored material design. We anticipate that the exceptional electronic properties of K2AgBiI6 will not only redefine the boundaries of materials engineering but also catalyze unprecedented advances in sustainable technology. Employing the powerful computational tool CASTEP, we conducted detailed electronic structure calculations within the framework of Density Functional Theory (DFT) to unravel the electronic properties of the double perovskite K2AgBiI6. Our investigation thoroughly explored structural properties, band structure, total density of states (DOS), and partial density of states (PDOS). Furthermore, we systematically examined the influence of different exchange-correlation functionals, including LDA, GGA, and m-GGA, on the electronic and optical features of the material by presenting a comparative analysis of these approximations.